DOI: 10.11606/d.25.2019.tde-23012019-161605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mechanical behavior between conventional NiTi, CM, M-Wire and CM-EDM alloy instruments for cyclic fatigue and torsion fracture - evaluation of fracture surface in scanning electron microscope

Abstract: Electron Microscope Comparação do comportamento mecânico entre instrumentos de liga NiTi convencional, CM, M-Wire e CM-EDM quanto a fratura por fadiga cíclica e por torção -Avaliação da superfície da fratura em Microscópio Eletrônico de Varredura BAURU 2018 RENAN DIEGO FURLAN Comparação do comportamento mecânico entre instrumentos de liga NiTi convencional, CM, M-Wire e CM-EDM quanto a fratura por fadiga cíclica e por torção -Avaliação da superfície da fratura em Microscópio Eletrônico de Varredura Comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
1
Order By: Relevance
“…However, some studies have reported that this surface nish has an effect on the crack initiation process [32] and structural irregularities of the instrument surface may compromise its integrity during clinical use, making the les more susceptible to fracture [7], while others have shown that the cyclic fatigue associated with EDM was signi cantly greater than that for the conventionally manufactured CM les [20]. In the present study, EDM les showed better resistance to cyclic fatigue than the other les, which is in agreement with the ndings of several studies [12,33,34], but its resistance was still lower than that of the CM les, which is inconsistent with other ndings [35]. On the other hand, the EDM le showed a signi cantly longer fractured fragment length and separated at a larger diameter than all other les in both single and double canal curvatures.…”
Section: Discussioncontrasting
confidence: 52%
“…However, some studies have reported that this surface nish has an effect on the crack initiation process [32] and structural irregularities of the instrument surface may compromise its integrity during clinical use, making the les more susceptible to fracture [7], while others have shown that the cyclic fatigue associated with EDM was signi cantly greater than that for the conventionally manufactured CM les [20]. In the present study, EDM les showed better resistance to cyclic fatigue than the other les, which is in agreement with the ndings of several studies [12,33,34], but its resistance was still lower than that of the CM les, which is inconsistent with other ndings [35]. On the other hand, the EDM le showed a signi cantly longer fractured fragment length and separated at a larger diameter than all other les in both single and double canal curvatures.…”
Section: Discussioncontrasting
confidence: 52%